The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1093/ajcn/nqab086
|View full text |Cite
|
Sign up to set email alerts
|

Gestational weight gain in 4 low- and middle-income countries and associations with birth outcomes: a secondary analysis of the Women First Trial

Abstract: Background Adequate gestational weight gain (GWG) is essential for healthy fetal growth. However, in low- and middle-income countries, where malnutrition is prevalent, little information is available about GWG and how it might be modified by nutritional status and interventions. Objective We describe GWG and its associations with fetal growth and birth outcomes. We also examined the extent to which prepregnancy BMI, and preco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 17 publications
3
14
0
1
Order By: Relevance
“…Poor fetal growth has been associated with an increased risk of mortality, morbidity, and adverse neurodevelopmental consequences later in life [4, 5, 7], whereas excessive fetal growth has been associated with poor maternal perinatal outcomes (e.g., cesarean section) and childhood obesity [1, 28]. The associations of GWG with birth length and head circumference, however, have rarely been evaluated [23, 29, 30]. Inadequate GWG in this study was positively associated with the risk of stunting and microcephaly at birth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor fetal growth has been associated with an increased risk of mortality, morbidity, and adverse neurodevelopmental consequences later in life [4, 5, 7], whereas excessive fetal growth has been associated with poor maternal perinatal outcomes (e.g., cesarean section) and childhood obesity [1, 28]. The associations of GWG with birth length and head circumference, however, have rarely been evaluated [23, 29, 30]. Inadequate GWG in this study was positively associated with the risk of stunting and microcephaly at birth.…”
Section: Discussionmentioning
confidence: 99%
“…A longitudinal study of 670 pregnant women in The Gambia similarly found that greater GWG at any level was positively associated with head circumference, but only greater GWG above a threshold of 0.5 SD of conditional weight gain (i.e., greater than the expected change in weight in a 3-month interval) was associated with higher birthweight and length, suggesting that better maternal nutrition (as measured by higher GWG) may be prioritized for brain growth over other anthropometric parameters [23]. Secondary data from analysis of a multicountry prenatal nutrition supplementation trial conducted in the Democratic Republic of the Congo, Guatemala, India, and Pakistan also found that higher GWG in the first trimester and higher GWG velocity overall were positively associated with birth length and weight [29].…”
Section: Discussionmentioning
confidence: 99%
“…In LMICs, improved GWG (100 g/wk) was associated with significantly improved birthweight and length, as was baseline prepregnancy BMI, early weight gain, and GWG from 12 to 32 weeks of gestation. 174 …”
Section: Growing Evidence Indicates That Maternal Prepregnancy Body M...mentioning
confidence: 99%
“…These changes, together with those observed in Ruminococcaceae and Lachnospiraceae in Guatemala, suggest that these putative SCFA-producing bacteria may be related to glycemic control during pregnancy, and a reduction in abundance might be beneficial for glucose regulation. In the WF participants, who on average had relatively low gestational weight gain and BMI ( Bauserman et al, 2021 ), these genera decreased during pregnancy. Future research, for example, utilizing germ-free mice, is needed to explore the potential causal relation between these SCFA producers and glycemic control during pregnancy.…”
Section: Discussionmentioning
confidence: 93%